Kekuasaan dan Moral dalam Pandangan Politik Niccolo Machiavelli - Mukhtar, Mukhtar (Al-Ijtima`i: International Journal of Government and Social Science, 2017)
This study discusses the concept of understanding the moral hearts political views Power Niccolo Machiavelli. Complete named Leonardo Niccolo Machiavelli was born in Florence (Firenze), Italy, 3 May 1469 and commonly referred to by name in the "Machiavelli" is the Son of Renaissance. He mocks A Lawyer Bernardo who came from aristocratic family, and grew up in Florence, Italy. In his book, The Prince (The Lord), Niccolo Machiavelli indicates that to be a ruler should do everything they can. He also gives advice on how to become a ruler who can maintain his power by ignoring the permanence ratings of morality and religion. Machiavelli separates between state power with religious life and moral interests. He only discusses how to achieve the goal of power no matter what. Machiavelli argued that power and morality are two separate things. Moral assumptions regarded as a stand-alone entity. Morality is part of a strategy of power, which is not always associated with good and bad issues yet to be realistic and objective and not universal, he could have choppy every time depending on the condition of society.